2016
DOI: 10.4269/ajtmh.15-0627
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Genotype Distribution in the Northern Territory, Australia

Abstract: Melioidosis is a tropical disease of high mortality caused by the environmental bacterium, Burkholderia pseudomallei. We have collected clinical isolates from the highly endemic Northern Territory of Australia routinely since 1989, and animal and environmental B. pseudomallei isolates since 1991. Here we provide a complete record of all B. pseudomallei multilocus sequence types (STs) found in the Northern Territory to date, and distribution maps of the eight most common environmental STs. We observed surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Despite this, ST-36 and ST-109 comprised nearly 50% of the 135 isolates examined and ST-327 and ST-553 were the only additional molecular types for which we identified more than five isolates. These results are consistent with previous studies suggesting genetic diversity and abundance can vary amongst different B. pseudomallei STs and that there is an overrepresentation of a few STs within the Darwin region 6,9 . Five STs have been shown to comprise 90% of the overall clinical and environmental isolate abundance in Darwin and consistent with this, three of these were the most frequently identified molecular types in this study (ST-36, ST-109 and ST-553) 9 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Despite this, ST-36 and ST-109 comprised nearly 50% of the 135 isolates examined and ST-327 and ST-553 were the only additional molecular types for which we identified more than five isolates. These results are consistent with previous studies suggesting genetic diversity and abundance can vary amongst different B. pseudomallei STs and that there is an overrepresentation of a few STs within the Darwin region 6,9 . Five STs have been shown to comprise 90% of the overall clinical and environmental isolate abundance in Darwin and consistent with this, three of these were the most frequently identified molecular types in this study (ST-36, ST-109 and ST-553) 9 .…”
Section: Discussionsupporting
confidence: 93%
“…We also found significantly more ST-36 in soil compared to water, collectively suggesting that the ST is well-established in the urban Darwin environment and this may be why we observed no spatial clustering for the strain. Interestingly, while ST-109 is also one of the region's most frequently identified and widely dispersed molecular types, particularly in rural Darwin which was not included in this study, we observed a significant cluster within the city urban centre 6,9,17 . Since construction and earthwork projects have substantially increased in urban central Darwin in recent years, soil disturbance may have caused the strain to resurface and spread throughout the urban area.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations